The new derivative of 1,2,4-triazoly antimicrobial action study - Киричко, Б. П.; Звенігородська, Т. В.; Парченко, В. В. (Scientific Progress & Innovations, 2012)
The new derivative of 1,2,4-triazoly – AИ 99 and AИ 100 combinations – antimicrobial action has been study. The microbial sensitiveness of present combinations has done by diffusion technique of agar by use special made disks. The AИ 99 and AИ 100 combinations antimicrobial action of 0,5-1% concentration has been established. Most expressive antimicrobial action AИ 99 and AИ 100 combinations have been against Corinobacter pseudodiphteridicum, Str. pyogenes and Staph. spp, and weak with reference to P. vulgaris and E. coli.